Bilayered silk/silk-nanoCaP scaffolds for osteochondral tissue engineering: in vitro and In vivo assessment of biological performance - Yan, Leping (2015)
Novel porous bilayered scaffolds, fully integrating a silk fibroin (SF) layer and a silk-nano calcium phosphate (Silk-NanoCaP) layer for osteochondral defect (OCD) regeneration were developed. Homogeneous porosity distribution was achieved in the scaffolds, with calcium phosphate phase only retained in the Silk-NanoCaP layer. The scaffold presented compressive moduli of 0.4 MPa in wet state. Rabbit bone marrow mesenchymal stromal cells (RBMSCs) were cultured on the scaffolds, and good adhesion and proliferation were observed. The Silk-NanoCaP layer showed a higher alkaline phosphatase level than the silk layer in osteogenic conditions. Subcutaneous implantation in rabbits demonstrated weak inflammation. In a rabbit knee critical size OCD model, the scaffolds firmly integrated into the host tissue. The histological analysis and immunohistochemistry analysis showed that collagen II positive cartilage and glycosaminoglycan regeneration presented in the silk layer, and de novo bone ingrowths and vessel formation were observed in the Silk-NanoCaP layer. These bilayered scaffolds can therefore be promising candidates for OCD regeneration.